The effects of pollution on open access fisheries: A case study of the Black Sea - Duncan Knowler; Edward B. Barbier; Ivar E. Strand (Fondazione Eni Enrico Mattei (FEEM), 1997)
There is now increasing recognition that the world's marine ecosystems, especially coastal areas and semi-enclosed seas, are suffering from degradation and modification due to human influences. One of the most serious problems is nutrient enrichment, which in the long term harms productivity and damages the ecosystem. Concurrent with this degradation is a rising awareness of the role of overfishing in the demise of global marine fish stocks, especially where property rights are poorly defined and open access prevails in the fishery. In some regions, such as the Black Sea, the two actions together have led to collapses in fish stocks. However, there has been little investigation of the linkage between the two problems to date. In this paper, we assess the non-efficiency benefits of improving environmental quality in the presence of such linkages, recognising that efficiency benefits may not be significant under the circumstances describing many open access fisheries. We use a dynamic bioeconomic modelling approach which incorporates habitat quality explicitly, first theoretically analysing the comparative static effects of an exogenous reduction in nutrient inputs and then empirically demonstrating the approach using a case study of Black Sea anchovy. The methodology, which may have a wider application to fisheries-pollution problems, allows us to show that pollution abatement significantly raises harvest, employment and revenues at the long run equilibrium of the system. Ultimately, for substantial efficiency benefits to arise from addressing the nutrient enrichment problem requires that the open access problem be addressed as well.
Keywords: Q2; Q20; Q22; 330; Anchovy; Black Sea; Bioeconomic; Coastal; Ecological; Economics; Eutrophication; Fisheries; Jellyfish; Marine; Nutrients; Open access; Pollution; Turkey; Fischereiressourcen; Ressourcenökonomik; Meeresverschmutzung; Theorie; Schwarzes Meer